2000
DOI: 10.1111/j.1559-1816.2000.tb02432.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Gender Biases on Actual Job Performance of Real People: A Meta‐Analysis1

Abstract: This study examined gender bias on job performance in work settings where confounding variables (e. g., organizational level, experience, education) were cautiously taken into consideration to ensure fair comparisons. Although previous meta‐analyses examined gender biases on evaluations, findings in tightly controlled laboratory environments may differ from those in highly complicated field studies. We found little evidence of overall gender bias in performance appraisals in nonconfounded field studies. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 66 publications
(69 reference statements)
6
147
0
2
Order By: Relevance
“…Second, female leaders became less effective relative to male leaders as the proportion of male subordinates increased, perhaps reflecting male (vs. female) subordinates' construal of leadership in more masculine terms and greater approval of traditional gender roles. Third, the greater the proportion of men among the raters whose data produced the measures of effectiveness (these raters were not necessarily leaders' subordinates), the less was the effectiveness of women relative to men (see Bowen, Swim, & Jacobs, 2000, for a similar effect). Fourth, women were substantially less effective than men in military organizations, a traditionally masculine environment, but modestly more effective than men in organizations in the domains of education, government, and social service.…”
Section: Studies Of Leader Effectivenessmentioning
confidence: 99%
“…Second, female leaders became less effective relative to male leaders as the proportion of male subordinates increased, perhaps reflecting male (vs. female) subordinates' construal of leadership in more masculine terms and greater approval of traditional gender roles. Third, the greater the proportion of men among the raters whose data produced the measures of effectiveness (these raters were not necessarily leaders' subordinates), the less was the effectiveness of women relative to men (see Bowen, Swim, & Jacobs, 2000, for a similar effect). Fourth, women were substantially less effective than men in military organizations, a traditionally masculine environment, but modestly more effective than men in organizations in the domains of education, government, and social service.…”
Section: Studies Of Leader Effectivenessmentioning
confidence: 99%
“…For example, future research may explore whether evaluator-applicant similarity on discriminable characteristics affects the stereotypes and prototypes evaluators use when evaluating applicants. Research suggests that rater x ratee interactions can affect the magnitude of discrimination (Bowen et al, 2000), and these interactions may also be relevant to predicting evaluators' stereotypes and prototypes. In applying the prototype matching model, it is also important that future research explore the role of contextual factors such as how prototypes differ between jobs other than sales and customer service, and how the prototype matching model generalizes to work-related settings beyond that of selection.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…However, meta-analyses of field research have also shown an advantage for females in Two points become salient from the lab-and field-based sex discrimination research described above. First, the practical significance of sex difference findings has typically been described as small (i.e., Bowen et al, 2000;Davison & Burke, 2000;Dean et al, 2008;Olian et al, 1988;Roth et al, 2008;Swim et al, 1989). However, these seemingly small practical differences have been argued to have greater long term effects (Agars, 2004;Eagly, 1995).…”
Section: Sex and Weight Discriminationmentioning
confidence: 99%
See 2 more Smart Citations